MILLENNIAL FINANCIAL MANAGEMENT DURING A PANDEMIC COVID 19 GOLD INVESTMENT CASE STUDY - gita putri astari (Scientia Integritas Utama, 2022)
Gold investment is a safe investment for beginners and suitable for millennials, gold investment is the easiest besides good returns the risk is also smaller and can be a hedge during a crisis. Many factors cause millennials to choose gold as an investment tool. In addition to selling gold bars in small quantities starting from 0.1 gr from antam, mini gold, EOA gold, Lotus Archi and so on which is a convenience for all people to start investing, digital gold savings is also a facility that makes it easier for investors to make transactions with flexible locations. This is also supported by the phenomenon of gold prices which every year experience a significant increase, increasing millennial interest in starting to invest in gold. The research method used, namely descriptive qualitative, will provide an overview (description) of an event or symptom of data and information which is then associated with theories and concepts that support the discussion, where this explanation uses qualitative methods with a theoretical approach to Financial Management, and Gold Investment. The nature of research is explanatory research where the object of research is individual. The results of this study explained that there is no significant difference between the rate of return between gold investment and stock investment, there is no significant difference between risk between gold investment and stock investment, the gold rate of return is higher than the stock return. In both returns, there is a difference where the average gold investment is better (high) compared to the stock return investment, the gold risk level is greater than the stock risk level. In both risks there is a difference where the average gold investment is higher than the risk s investment.